2004
DOI: 10.1016/j.jacc.2003.09.051
|View full text |Cite
|
Sign up to set email alerts
|

Clinical significance of brain natriuretic peptide in primary pulmonary hypertension

Abstract: Our data suggest that plasma BNP levels are closely related to the functional impairment of PPH patients and parallel the extent of pulmonary hemodynamic changes and right heart failure. Serial measurements of plasma BNP concentrations may help improve the management of PPH patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
128
4
9

Year Published

2006
2006
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 256 publications
(150 citation statements)
references
References 36 publications
9
128
4
9
Order By: Relevance
“…It has been observed in the previous studies that excessive increases occur in the plasma levels in the presence of especially left ventricular dysfunction [7,8]. In subsequent studies, it has been found that plasma BNP level elevates in proportion to the extent of the right ventricular dysfunction in diseases, like primary pulmonary hypertension, cor pulmonale and pulmonary emboli that affect the pulmonary bed and the right heart [9][10][11]. Since MS is a disease affecting the right heart, it is expected to raise BNP.…”
Section: Introductionmentioning
confidence: 95%
“…It has been observed in the previous studies that excessive increases occur in the plasma levels in the presence of especially left ventricular dysfunction [7,8]. In subsequent studies, it has been found that plasma BNP level elevates in proportion to the extent of the right ventricular dysfunction in diseases, like primary pulmonary hypertension, cor pulmonale and pulmonary emboli that affect the pulmonary bed and the right heart [9][10][11]. Since MS is a disease affecting the right heart, it is expected to raise BNP.…”
Section: Introductionmentioning
confidence: 95%
“…62,66,[90][91][92][93] For example, as discussed above, studies have demonstrated neurohormonal changes in adults and children with CHD similar to those in acquired HF. 62,66,90,91 Therapies that reverse remodeling or slow the remodeling process were shown to improve survival in patients with LV systolic dysfunction caused by acquired heart disease.…”
Section: Hf Pharmacotherapy Applied In Chdmentioning
confidence: 93%
“…6 The proteins BNP/N-terminal pro b-type natriuretic peptide are associated with pulmonary hemodynamics and right ventricular dysfunction in PH, and BNP levels within World Health Organization functional class II do not increase. [22][23][24] We previously reported that sLR11 is produced by immature, but not by mature, SMC, in atherosclerotic arteries and that LR11 mRNA expression is high in human CD34 + and …”
Section: Soluble Lr11 As a Biomarker Of Proliferative Smc In Patientsmentioning
confidence: 99%